Perbandingan Kemampuan Problem Solving pada Anak Usia 4-5 Tahun Antara Stimulasi Bermain Terstruktur dan Bermain Bebas di Kota Denpasar - Sindy Firdaus; I Gede Eka Juli Prasana; Indah Pramita; Sayu Aryantari Putri Thanaya (Universitas Pahlawan Tuanku Tambusai, 2026)
Problem-solving ability is a part of cognitive development that plays an important role in children’s ability to think, understand, and solve simple problems according to their developmental stage. Technological advancement has led to increased gadget use among early childhood children, which may reduce play activities and potentially result in suboptimal cognitive development, including problem-solving abilities. Children aged 4–5 years are in the early preschool phase, a crucial period in development, where appropriate play stimulation is needed to support cognitive growth. Structured play stimulation provides goal-directed activities aligned with developmental objectives, while free play allows children to explore independently. Objective: This study aimed to compare problem-solving abilities among children aged 4–5 years who received structured play stimulation and those who engaged in free play activities in Denpasar City. Methods: This study used an analytical observational design with a comparative cross-sectional approach. The sample consisted of 140 children aged 4–5 years divided into two groups using purposive sampling technique. Problem-solving ability was measured using the Ages and Stages Questionnaire-3 (ASQ-3) problem-solving domain, while the Dimensional Change Card Sort (DCCS) was used as a control variable. Statistical analysis was performed using the Mann–Whitney U test. Results: A significant difference in problem-solving ability was found between the structured play group and the free play group (p=0.003), with the structured play group showing a higher mean rank (78.69) compared to the free play group (62.31). Conclusion: There was a significant difference in problem-solving ability among children aged 4–5 years between the structured play group and the free play group. Structured play stimulation demonstrated better outcomes in supporting problem-solving abilities among preschool-aged children.